IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH UMUM (SMU) (Problematika dan Pemecahannya) - *, Ismail (Forum Tarbiyah, 2009)
Islamic Religious Education (PAI) essentially has the fundamental duty to explore, analyze, develop and introduce the teachings of Islam based on Qur’an and hadith. Hence, Islamic Religious Education (PAI) is required to implement new approaches and orientations that are relevant to contemporary conditions, without ignoring the values of Islamic teaching. But in practice, the transcendence of Islamic Religious Education (PAI) has been lost while juxtaposed with High School (SMU). There are at least three main elements that influence the formation of character Islamic Religious Education (PAI) in high school, among others: Teachers, Students, and Environment (space and time). Thus, the success or failure of Islamic Religious Education (PAI) in high school depends on the mutual relations of those all three.